การนำสัญญาอนุญาตให้ใช้เครื่องหมายการค้าเป็นหลักประกัน - สิริรัตน์ สารี (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The licensee’s right under a trademark license agreement is considered as a property under Section 138 of the Civil and Commercial Code of Thailand. It is also categorized as an intangible asset according to the Accounting Standard No. 38. There are three methods for valuation of licensee’s right as follows: 1) The Cost Approach, 2) The Comparison/Market Approach and 3) The Income Approach. The third method is the most appropriate method for valuation of intangible assets, including trademarks license rights.This thesis studies the most appropriateness of using trademarks license agreement as collaterals, including its enforcement. The study finds that the transfer of right or contracts ofwhich the licensee agrees to transfer its trademark license right to its creditor is only a contractual right between the parties of the contract. In other words, it does not entitle the creditor a preferential right over the collateral. Moreover, the concepts of collateral which create a creditor’s preferential right under the Civil and Commercial Code such as mortgage and pledge cannot be applied with trademarks license agreement as it is intangible property.The researcher is of the opinion that using a trademark as collateral should be allowed under the draft of the Secured Transaction Act B.E…. Under the act, the grantor is not required to handover the collateral to the grantee and the grantor retains the right to seek benefits from the collateral during the secured transaction. Furthermore, the grantee is considered as a secured creditor. Therefore, recommendations to support the use of licensee’s right as collateral are as follows: 1) the licensor’s prior consent to the use of licensee’s right as collateral shall be obtained, 2) the draft of the Secured Transaction Act B.E… Section 8 (5) should include trademark licensee’s right as a type of collateral, 3) enforcement of licensee’s right as collateral should be conducted by auction together with allowing sub-licensing, 4) measures to protect grantee should be provided in secured transaction agreement.